Assessing the Philippine Coast Guard's Visit, Board, Search, and Seizure (VBSS) Procedures: Operational Status, Influencing Factors, and Challenges - Benjamin A. Misador Jr. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study assessed the operational status, influencing factors, and challenges encountered in the implementation of the Philippine Coast Guard's Visit, Board, Search, and Seizure (VBSS) procedures for maritime law enforcement. Specifically, it examined the status of VBSS procedures in terms of operators' capability, technology application, procedural adherence, and legal compliance, as well as the effectiveness of VBSS implementation and the challenges encountered by operators. The study employed a mixed-methods research design using a convergent parallel approach. Quantitative data were collected from 305 Philippine Coast Guard operators directly involved in VBSS operations, while qualitative data were obtained through semi-structured interviews with 18 interview participants composed of 15 operational officers/team leaders and three legal experts. Data were analyzed using descriptive statistics and thematic analysis. The findings revealed that VBSS procedures were generally implemented effectively. Operators demonstrated high levels of capability, procedural adherence, and legal compliance, while technology application emerged as the area requiring the greatest improvement due to limitations in operational equipment and technological resources. The qualitative findings further identified challenges related to resource constraints, operational conditions, and legal and procedural concerns affecting VBSS implementation. The study concludes that strengthening operators' capability, enhancing technological resources, and sustaining procedural and legal compliance are essential to improving VBSS implementation. It recommends continuous competency-based training for operators, modernization of operational resources, strengthened legal capability, and enhanced inter-agency coordination to further improve maritime law enforcement operations.